Continuous measurement of porcine renal cortex microcirculation with enhanced thermal diffusion technology - Kraus, Thomas W.; Klar, Ernst; Osswald, Brigitte; Pinto Fernandes, Luiz; Mehrabi, Arianeb; Gebhard, Martha-Maria; Herfarth, Christian (Journal of surgical research, 1996)
Continuous monitoring of renal cortical blood flow (RCBF) in the perioperative setting of aortic or renal vascular surgery could faciliate the early detection of vascular complications, possibly resulting in a reduction of postoperative renal failure. A new prototype system for measurement of parenchymous organ perfusion based on the principle of thermal diffusion (“TD”—Thermal Diffusion Electrode, Thermal Technologies Inc., Cambridge, MA, USA) was used for RCBF measurements in the outer cortex of the porcine kidney. We validated the sensitivity of the device to detect renal blood flow impairment, comparing TD flow data with renal artery blood flow values (RABF), measured by ultrasonic flow probes. The hypothesis was tested that acute disturbances of RCBF, induced by a variable degree of renal artery stenosis, can be immediately detected and continuously monitored by TD measurements in the porcine renal cortex. Mean baseline RCBF measured by TD electrodes was 68.1 ± 25.0 ml/100 g/min. Mean baseline RABF was 102.1 ± 26.6 ml/min. Controlled induction of a variable degree of renal arterial occlusion by implanted vascular balloon occluders was always followed by an immediate and proportional decline of RCBF, as measured by TD. Flow data obtained with both methods were significantly correlated by linear regression (r= .82,r2= .68;P< 0.0001). Dynamic changes of RABF in the time course of renal artery partial/total occlusion and arterial flow release could be continuously followed by detection of corresponding flow changes of RCBF. We conclude that the TD system investigated in the current study allows a continuous and sensitive determination of porcine renal cortex perfusion. A clinical evaluation of the method, e.g., in the perioperative setting of aortic or renal transplantation surgery, now appears to be justified.